Integrating Wordwall as a Digital Tool to Support Students’ Engagement in English Language Learning - Rachel Mujahid; Sitti Khadiijah; Faida Azhimia; Faisal Rahman (Majalah Ilmiah METHODA, 2025)
This study was motivated by the limited engagement of tenth-grade students at MAN 3 Banjarmasin during English learning activities. The research aimed to explore how the integration of Wordwall as a digital learning tool could enhance students’ engagement in the English classroom. This study applied a qualitative Classroom Action Research (CAR) design conducted in one cycle, consisting of planning, acting, observing, and reflecting. The participants were 29 students from class X-F. Data were collected through observation sheets, questionnaires, and documentation. The findings revealed that the use of Wordwall successfully improved students’ engagement across cognitive, emotional, and behavioral dimensions. Students showed greater focus, enthusiasm, and behavioral engagement in learning activities. Therefore, it can be concluded that Wordwall, as a digital learning tool, plays a significant role in fostering a more interactive and engaging English learning environment.